Electromagnetic wave propagation and scattering in rain and other hydrometeors - Oguchi, T. (Proceedings of the IEEE, 1983)
This paper reviews the theories and the results of numerical calculations of interactions between hydrometeors and microwaves or millimeter waves propagating in media containing these hydrometeors. At frequencies above about 5 GHz, rain, snow, or ice crystals in high altitudes cause various degrading effects on the performance of communication links. The attenuation of the transmitted signals is a well-known example of such effects. Because of the demand for more communication channels, operating frequencies of both terrestrial and earth--scace communication systems become increasingly higher, and the communication technology becomes more and more sophisticated with the use of digital techniques, or the use of both orthogonaly polarized channels. These have given rise to the need of acquiring more detailed knowledge of interactions between hydrometeors and waves than is necessary for the calculation of attenuation. To obtain such knowledge, we have to know the detailed microphysical properties of hydrometeors, such as shape, size distributions, or the motion of hydrometeors while they are falling. These properties, some obtained previously by meteorolgists and some obtaianed recently by radio engineers to meet the requirements of present radio problems, are reviewed first. Various methods of calculations, and the detailed knowledge obtained from calculations of the single scattering properties of hydrometeors, whose sizes are generally comparable to wavelength, are then reviewed. With the information of these scattering properties, various propagation phenomena are discussed from a theoretical point of view. Specific subjects treated include attenuation, cross polarization due to rain or ice crystals in high altitudes, the methods of depolarization cancellation, rain scattering other then forward and backward which is necessary in the estimation of rain scatter interference between two communication links operating at the same frequency, various multiple or incoherent scattering effects on copolar and cross-polar signals, pulse shape, channel transfer characteristics, etc. The aim of this review is to provide fundamental background informations on the interactions between hydrometeors and radio waves, and hence the more practical investigations, such as long-term statistics of attenuation, are beyond the scope of this review.